Unlocking the Functional Mechanics of Gas Turbine Plants: Enhancing Reliability, Efficiency, and Environmental Sustainability - Onyewudiala Ibeawuchi Julius; Samuel Hanotu Kwelle.; Nnadikwe Johnson (SEAN Institute, 2025)
Abstract. Gas turbine plants play a vital role in modern society's energy generation, with a focus on reliability, efficiency, and sustainable development. This research aims to investigate and enhance the operational principles of gas turbine plants to achieve these objectives. The study begins by examining the current operational practices and challenges faced by gas turbine plants, highlighting the need for continuous improvement. Factors influencing the reliability of gas turbine plants are analyzed, and strategies for enhancing reliability are proposed to ensure uninterrupted power supply. Efficiency is a key focus of the research, with an evaluation of the performance of gas turbine plants using equations such as η = 1 - (1/r^(γ-1)/γ) to identify areas for optimization. By maximizing efficiency, cost savings can be achieved, and environmental impact reduced, contributing to sustainable development. Environmental sustainability is another crucial aspect of the study, with an assessment of the environmental impact of gas turbine plants and exploration of measures to minimize emissions, resource consumption, and promote eco-friendly practices. Innovative technologies and best practices for improving the operational efficiency of gas turbine plants are investigated, including the use of regenerators with effectiveness ε = (T_hot,in - T_hot,out) / (T_hot,in - T_cold,in) and heat transfer equations Q = m × (h2 - h1). The research culminates in a set of recommendations and guidelines for enhancing the overall performance and sustainability of gas turbine plants, aligning with industry standards and environmental regulations. By achieving the objectives outlined in this research, we aim to contribute to the advancement of gas turbine plant operations, fostering reliable, efficient, and environmentally sustainable energy generation practices for a better future